SarA based novel therapeutic candidate against Staphylococcus aureus associated with vascular graft infections - Arya, Rekha; Ravikumar, R.; Santhosh, R. S.; Princy, S. Adline (Frontiers in Microbiology, 2015)
Staphylococcus aureus is a common pathogen seen in prosthetic vascular graft, leading to high morbidity and mortality. The virulence genes for severity of infections are under the control of global regulators. Staphylococcal accessory regulator A (SarA) a known master controller of biofilm formation is an attractive target for the drug development. A structure based screening of lead compounds was employed for the identification of novel small molecule inhibitors targeted to interact to the DNA binding domain of the transcriptional activator, SarA and hinder its response over the control of genes that up-regulate the phenotype, biofilm. The top-hit SarA selective inhibitor, 4-[(2,4-diflurobenzyl)amino] cyclohexanol (SarABI) was further validated in-vitro for its efficacy. The SarABI was found to have MBIC50value of 200 μg/ml and also down-regulated the expression of the RNA effector, (RNAIII), Hemolysin (hld), and fibronectin-binding protein (fnbA). The anti-adherence property of SarABI on S. aureus invasion to the host epithelial cell lines (Hep-2) was examined where no significant attachment of S. aureus was observed. The SarABI inhibits the colonization of MDR S. aureus in animal model experiment significantly cohere to the molecular docking studies and in vitro experiments. So, we propose that the SarABI could be a novel substitute to overcome a higher degree of MDR S. aureus colonization on vascular graft.